Thiamine Diphosphate Dependent KdcA‐Catalysed Formyl Elongation of Aldehydes. Issue 17 (25th July 2019) - Germer, Philipp; Gauchenova, Ekaterina; Walter, Lydia; Müller, Michael
Abstract: The formose reaction, one of the oldest name reactions in organic chemistry, uses formaldehyde as a C1 unit resulting in different monosaccharides and sugar‐like compounds. Nucleophilic formyl elongation is an attractive option to obtain 1, 2‐functionalised building blocks for organic synthesis and pharmaceuticals; however, it has rarely been applied in asymmetric catalysis. The thiamine diphosphate dependent enzyme 2‐keto acid decarboxylase (KdcA) from Lactococcus lactis is able to transfer formyl units to aliphatic and aromatic aldehydes, both in an electrophilic and in a nucleophilic way. We have established the formation of unstable chiral 2‐hydroxy aldehydes by subsequent modifications (chemical derivatisation with 2, 4‐dinitrophenylhydrazine, ( R )‐Mosher's acid chloride) or by enzymatic trapping (oxidation and reductive amination). Abstract : Mighty enzymes : Nucleophilic and electrophilic formyl elongation of aromatic and aliphatic aldehydes is catalysed by thiamine diphosphate dependent 2‐keto acid decarboxylase. The presence of unstable aromatic mandelic aldehyde in aqueous solution could be proved indirectly via LC‐MS/MS analysis.